Analysis of the promising speech act used in President Jokowi’s speech at the visi Indonesia event - Nada, Qotrun; Yorike, Dias Bulqis; Tsaaniyah, Lailatus Sa’aadatis (Maliki Interdisciplinary Journal, 2023)
This paper discusses the types of promising speech acts based on the theory Searle (1985) put forward in President Jokowi’s speech at the Visi Indonesia program, which was broadcast on Net TV in 2019. This research aims to identify the types of promising speech acts used in conveying the country’s future development efforts promised by President Jokowi after he was elected president of Indonesia. The study results show that eleven utterances fulfill the five requirements of the theory Searle (1985) put forward as promising speech acts in the speech. Further analysis also indicates the discovery of one promising speech act type utterance that uses persuasion techniques, seven promising speech act type utterances that use advocacy techniques, and three promising speech act type utterances that use persuasive storytelling techniques. The three types of techniques used in the speech give an impression that makes listeners confident, excited and changes their views on an issue being discussed.